Pengaruh Konsep Diri Sebagai Prediktor Kesehatan Mental Mahasiswa - Budiyati, Endah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This research explores the relationship between self-concept and mental health of students in a higher education environment. A literature review was conducted to develop an in-depth understanding of how self-concept, which includes individuals' evaluation of themselves, can influence mental health. Key findings suggest that positive self-concept is correlated with good mental health, while academic environmental factors and academic achievement also have a significant impact. This research highlights the importance of developing support and intervention programs that focus on forming a positive self-concept to improve student well-being.